Pengaruh Iklim Organisasi Terhadap Kinerja Karyawan Dengan Semangat Kerja Sebagai Variabel Intervening Pada Pt. Bank Pembangunan Daerah Jawa Timur Kota Kediri - Mahdi Noor Fatoni; Budi Rahayu; IGG Heru Marwanto; Enni Sustiyatik (Fakultas Ekonomi Universitas Kadiri, 2022)
This research has the objectives of, among others, finding out and analyzing the direct influence of Organizational Climate, knowing and analyzing the direct influence of organizational climate on Morale, knowing and analyzing the direct influence of Morale on Employee performance, knowing and analyzing the indirect influence of organizational climate on Employee performance through Morale at PT. East Java Regional Development Bank, Kediri City. The population in this study was all employees of PT. East Java Regional Development Bank Kediri City, which totals 250 people. The determination of the number of samples in this study used the Slovin formula. Then data collection techniques, data analysis techniques, research instrument tests, validation tests, reliability tests, and path analysis were carried out. From the calculation results, results were obtained, based on the results of the validation test of the organizational climate variable instrument, that all r-calculated values are greater than the r- table. This shows that the research instrument is said to be valid and can further be used in the study; the validation test of the working spirit variable instrument shows that all r-count values are greater than the r- table. This suggests that the research instrument is valid and can be used further in the study; the result of the instrument relibrium test that reliability test on the research variable instrument shows that all Cronbach‟s Alpha values are greater than 0.60. This suggests that the research instrument is reliable; the hypothesis test results can be concluded that the first hypothesis that reads Organizational climate affects employee performance is accepted since it has a statistical t value of 2.138> 1.98 (critical limit). Furthermore, the second hypothesis states that the organizational climate affects employee performance is accepted because it has a statistical t value of 2,220 > 1.98. The third hypothesis that Morale affects employee performance is accepted because it has a statistical t value of 10.049> 1.98. Furthermore, the fourth hypothesis, which reads that the organizational climate affects employee performance through Morale, is accepted because it has a statistical t value of 2.261 > 1.98 so that the fourth hypothesis is accepted